A chemical investigation of the leaves of Piper nigrum L. (Fam. Piperaceae) - Guerrero, Noemi Castro
By continuous extraction of the powdered and dried leaves of Piper nigrum L. (Fam. Piperaceae), three crude extracts were obtained - alcohol, ether, and ethyl acetate. Preliminary testings revealed the presence of alkaloids in both the alcohol and ether extracts. None of the extracts contained tannins. Only the alcohol extract contained flavonols, and only the ether extract contained sterols. TLC on the crude extracts, using a cyclohexane-ethyl acetate solvent system (1:1), indicated a similarity between the spot obtained from the ethyl acetate extract (ave. Rf: 0.61) and one of the three spots from the ether extract (ave. Rf: 0.63). using a petroleum ether-ether solvent system (1:1), the spot obtained from the alcohol extract (Rf: 0.81) showed some similarity to one of the two spots obtained from the ether extract (ave. Rf: 0.86). By column chromatography and using benzene as the eluting solvent, a chosen benzene fraction gave 6 spots using TLC analysis. Due to distinct separations, a preparative TLC was prepared and band number 7 was scraped off, dissolved in chloroform, filtered, concentrated then run in a UV spectrophotometer.